Autoaferição não orientada da pressão arterial sistêmica em pacientes hipertensos - Almeida, Glessiane de Oliveira (2021)
Introduction: Systemic Arterial Hypertension (SAH) is a public health problem and a cardiovascular risk factor. The routine practice of self-measurement of blood pressure (BP), not oriented with pulse devices, may not be precisely useful in controlling BP and may lead the patient to self-medicate erroneously. Therefore, it is necessary to evaluate an unguided BP self-measurement in real-life circumstances in hypertensive patients. Objectives: The objective of this study was to analyze the complications resulting from unguided selfmeasurement of systemic blood pressure in hypertensive patients, as well as to assess an association of BP self-measurement with trait / state anxiety; to evaluate the association of AP self-assessment with non-control of AP - unscheduled visits to urgency and self-medication; analysis of factors associated with blood pressure control; the differences between genders in anxiety and unscheduled visits to the emergency room of hypertensive patients. Method: Observational, cross-sectional and analytical study, carried out from June 2017 to October 2019, with 1000 hypertensive volunteers (age: 61.0 ± 12.5). Through a questionnaire and medical form, sociodemographic and clinical data (comorbidities, BP control) were collected on the use of the pressure device. Anxiety was assessed by the State-Trait Anxiety Inventory (STAI). In the analysis of the statistics, descriptive measures were used, such as absolute frequency, relative percentage, mean and standard deviation. Fisher's exact hypothesis tests, Pearson's χ², Student's t, and effect sizes d and h of Cohen were given. Crude ratios were estimated and adjusted using logistic regression. The software Statistical Package for the Social Sciences version 24.0 was used and the level of significance adopted was 5%. Results: About the groups that performed non-oriented self-measurement of BP, showed that they had higher frequencies of self-medication (57.9%, p <0.0001) and more unscheduled visits to the emergency room (68%, p <0.0001). In addition, a lower level of BP control (46.8%, p <0.0001) was associated with higher levels of anxiety (52.3%, p <0.0001) in the group that performed unguided self-assessments of the PA. The odds ratio of non-BP control and trait anxiety and state anxiety controlled by sex (OR: 1.705; 95% CI: 1.308 - 2.223; p <0.0001), use of medication for comorbidities (OR: 1.921; 95% CI: 1.481 - 2.493; p <0.0001), BP selfmeasurement (OR: 3.705; 95% CI: 2.827 - 4.856; p <0.0001) and Self-medication (OR: 2.029; 95% CI: 1.561 - 2.636; p <0.0001). State anxiety (ORa: 1,587; 95% CI: 1,200 - 2,098; p = 0,001) and trait anxiety (ORa: 1,605; 95% CI: 1,211 - 2,127; p = 0,001) were observed as a factor associated with not controlling hypertension blood pressure independently of sex, use of medications for comorbidities, self-measurement of BP and self-medication. In addition, we observed that females are significantly greater in terms of the presence of comorbidities (h = 0.134; p = 0.036), diabetes mellitus (h = 0.137; p = 0.034), dyslipidemia (h = 0.137; p = 0.032), depression (h = 0.240, p = 0.001), buy medicines at a popular pharmacy (h = 0.240; p <0.001), self-medication (h = 0.200; p = 0.002), unscheduled visit and trait anxieties (h = 0.290; p <0.001) and state (h = 0.239; p <0.001). In the multivariate analysis, females have a greater chance of unscheduled visits (OR: 1.43 (95% CI: 1.07-1.92), p = 0.015), higher levels of trait anxiety (OR: 1.59 (95% CI: 1.21-2.09) p = 0.001) and status (OR: 1.40 (95% CI: 1.06- 1.85) p = 0.016). Conclusion: The practice of non-oriented self-measurement of BP was associated with negative factors, such as high levels of anxiety and higher frequencies of selfmedication and unscheduled emergency visits. In addition, although women are more anxious, both State and Trait, men are the ones who most seek unscheduled visits to the emergency room.